Upaya ASEAN Terhadap Eksploitasi Anak Untuk Perdagangan Narkotika - Sopamena, Siska Vilonia Indah; Talaperuw, Vivi; Pattipeilohy, Quentyn Priscilla (Fakultas Hukum Universitas Pattimura, 2023)
Introduction: It is important to study child exploitation in the drug trade, its causes, and develop effective strategies to prevent and address this problem. ASEAN plays an important role for Southeast Asian countries fighting drug trafficking.Purposes of the Research: The purpose of this article is to study ASEAN's efforts in tackling the exploitation of children in the drug tradeMethods of the Research: Research for this article uses a normative juridical method, namely a method that examines and analyzes the substance of laws and regulations related to the subject matter of legal problems.Results of the Research: ASEAN's efforts in tackling the exploitation of children in drug trafficking are by prioritizing three essential things, namely policies, approaches and strategies, making sure that the views, approaches and coping methods used are aligned with the vision and mission of the ASEAN organization itself and can be approved by all members belonging to ASEAN. ASEAN’s efforts to this problematic phenomenon is by developing related legal products, cooperating with the Customs among countries, provide counseling on narcotics as a preventive measure, and more training to increase participation in these issues regionally.